Pengaruh Corporate Governance Dan Manajemen Laba Terhadap Kebijakan Dividen - Agustina Ratna Dwiati; Muhammad Bisyri Effendi (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractThe aim of this study is to test the impact of corporate governance and investment opportunity set toward dividend policy with earnings management as intervening variable. The sample of this study is non-financial firms listed in Indonesia Stock Exchange and also a member of Corporate Governance Perception Index on 2012 and 2013. The method that used in this study is multiple regression. The results showed that company with strong corporate governance really cared about shareholders interests by giving high dividend for them. Meanwhile, earnings management has no impact toward dividend policy.